User Satisfaction on The Efficacy of The Integrated Online Single Submission Management Information Systems - Alfian, Alfian; Murti, Galuh Tresna; Sarie, Putri Maulida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This research was conducted with the primary objective of examining the influence of user satisfaction on the efficacy of the Integrated Online Single Submission Management Information Systems in Indonesia Methodology/approach – This study employs a quantitative methodology, wherein data is gathered in numerical format, and hypothesis testing is carried out through statistical analysis. A survey that included information on user satisfaction was used to collect data from 44 members the association of business actors and licensing in Indonesia. The research was conducted online using a Google Form questionnaire, which was distributed to the Association of Business Actors and Licensing in Indonesia. In this research, the chosen data analysis method is simple linear regression analysis, designed to ascertain the correlation between a dependent variable and one independent variables. The quality of the data was evaluated through validity and reliability tests, ensuring the questionnaire instrument's soundness. The statistical analysis was conducted using the IBM Statistical Package for the Social Sciences (SPSS) version 26. Findings –The findings suggest that the effectiveness of the integrated licensing management information system is contingent upon user satisfaction. The results underscore the system's notable efficacy in terms of user satisfaction. Novelty/value – This study serves as a valuable tool for the assessment and enhancement of the Online Single Submission (OSS) Management Information System in Indonesia.